Kerangka Kebijakan Sosio-Budaya Menuju Pertanian 2025 ke Arah Pertanian Pedesaan Berdaya Saing Tinggi, Berkeadilan dan Berkelanjutan - Tri Pranadji (Forum penelitian Agro Ekonomi, 2004)
EnglishThe condition of rural agriculture recently facing some big problems in particular the weakness of social capital, poverty and environmental degradation which are progressively on large scale. Vision of agricultural development 2025 is sustaining rural welfare which is characterized by highly competitive, equity and sustainable. One of very important agricultural policies is how to improve rural socio-culture regarding to most of rural people good opportunity in higher level of quality of life. Therefore, agricultural development 2025 will strongly require a comprehensive framework of socio-culture policy. There are five primary elements of socio-culture which must be developed in agricultural development 2025, that are human competency (or high quality of human capital), strong local leadership, value system, health agribusiness organization (and management) at village level, and equal social structure (being based on agrarian resources domination). It is highly recommend that framework of socio-culture policy is constructed by combination between time reference of change and level of society in one side, and elements of socio-culture which are being transformed in the other side. Social capital, such as  rural law enforcement and governmental decentralization at rural level, have to be considered as the key to success in achieving rural community welfare. Some important aspects which must be paid attention to arrange good condition for running agriculture vision 2025 are to shift development orientation (from urban bias of non-agricultural resources based and footloose industrialization) toward rural industrialization base on local natural and human resources; agrarian reform base; strengthening of social control based on civil society; harmonization of partnership among government, rural-agricultural economic actors and community; and political arrangement which farmers have higher influence in political decision.IndonesianPertanian pedesaan saat ini masih menghadapi tiga masalah besar, yaitu lemahnya modal sosial, kemiskinan dan kerusakan sumberdaya pertanian yang semakin membesar. Visi pembangunan pertanian 2025 yang sesuai adalah pertanian pedesaan yang berdaya saing tinggi, berkeadilan dan berkelanjutan. Salah satu kebijakan pembangunan pertanian yang penting adalah kebijakan pemberdayaan sosio-budaya pedesaan. Oleh karena itu pembangunan pertanian 2025 membutuhkan kerangka kebijakan sosio-budaya yang komprehensif. Ada lima elemen sosio-budaya utama yang harus dikembangkan, yaitu: kompetensi SDM, kepemimpinan lokal, tata nilai, keorganisasian (dan manajemen) usaha tingkat desa dan struktur sosial (berbasis penguasaan sumberdaya agraria). Kerangka kebijakan sosio-budaya mengacu pada kombinasi antara tingkat masyarakat dan jangka waktu di satu sisi, dan elemen sosio-budaya yang ditransformasikan di sisi lain. Modal sosial, seperti penegakan sistem hukum pedesaan dan desentralisasi pemerintahan hingga tingkat desa, harus dianggap sebagai kunci sukses pencapaian kesejahteraan masyarakat pertanian pedesaan berkelanjutan. Beberapa hal yang harus diperhatikan untuk mengkondisikan visi pertanian 2025 terwujud, yaitu: perlunya mengubah orientasi pembangunan (dari industrialisasi non-pertanian yang footloose dan bias kota) menjadi yang memihak pada industrialisasi pedesaan berbasis pertanian dan perbaikan sumberdaya agraria di pedesaan; pentingnya reformasi keagrariaan; pengembangan kekuatan kontrol masyarakat madani (civil society); sinergi (harmonis) atau partnership antara pemerintah, pelaku usaha pertanian di pedesaan dan masyarakat lokal; dan tatanan politik yang memberi posisi layak bagi petani pedesaan.